Implementation of Transformation of SD IPS Learning Based on Augmented Reality (Ar) Assemblr : Literature Review on Design, Media, And Its Impact - Kiki Santoso; Isep Saepulloh; Lysda Reviyanti (Journal of Innovative and Creativity, 2025)
Transformation learning in the digital era demands approach innovative in the educational process , especially in learning Knowledge Knowledge Social Studies (IPS) in Elementary School . Research This aiming For to study in a way deep implementation Augmented Reality (AR) technology via the Assemblr platform in elementary school social studies learning . The method used is a qualitative literature study by analyzing 30 sources of accredited national and international journals and other academic documents published between 2018 and 2024. The results of the study indicate that AR-based learning design has interactive, multimodal, and contextual characteristics, very appropriate to the characteristics of elementary school students. The media developed through Assemblr is able to present social studies content in a concrete manner, especially on geography, history, and culture materials, thereby increasing student interest and motivation. Learning becomes more enjoyable and participatory. However, several obstacles were found such as limited infrastructure, low teacher digital literacy, and minimal local content. Nevertheless, the potential of AR Assemblr in improving student learning outcomes cognitively, affectively, and psychomotorically has proven significant. Therefore, it is recommended that there be intensive training for teachers, development of an adaptive curriculum, and systematic integration of AR into elementary school social studies learning. This study makes an important contribution to the development of digital learning media that is in accordance with the needs of elementary education in the technological era.